Are Publicly Available Online Businesses Lists Appropriate to be used as Sampling Frames in Croatian Business Surveys? - Žmuk Berislav (Business Systems Research, 2017)
Background: In order to conduct a probability business survey, a high quality sampling frame of enterprises is needed.